Identification of Shigella sp. in a Traditional Medicine Product - Dinda Putri Kunanti; Elsa Yuniarti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The high consumption of traditional medicine in Indonesia requires strict microbiological safety standards to prevent gastrointestinal infections caused by pathogenic bacteria such as Shigella sp. This study aimed to identify the presence of Shigella sp. in a traditional medicine product using selective media. The research was conducted at the Microbiology Laboratory of the Balai Besar Pengawas Obat dan Makanan Padang. One sample from batch number 08 of a traditional medicine product in form was processed through pre-enrichment, enrichment, and isolation stages using MacConkey Agar. The results showed that there was no growth of bacterial colonies with characteristics of Shigella sp. on the medium. Therefore, the tested sample was declared negative for Shigella sp. and met the microbiological safety requirements. These findings emphasize the importance of routine microbiological monitoring and confirmatory analyses across a broader range of production batches to maintain consistent product safety.